2017
DOI: 10.1101/gad.306753.117
|View full text |Cite
|
Sign up to set email alerts
|

Nup98 recruits the Wdr82–Set1A/COMPASS complex to promoters to regulate H3K4 trimethylation in hematopoietic progenitor cells

Abstract: Recent studies have shown that a subset of nucleoporins (Nups) can detach from the nuclear pore complex and move into the nuclear interior to regulate transcription. One such dynamic Nup, called Nup98, has been implicated in gene activation in healthy cells and has been shown to drive leukemogenesis when mutated in patients with acute myeloid leukemia (AML). Here we show that in hematopoietic cells, Nup98 binds predominantly to transcription start sites to recruit the Wdr82–Set1A/COMPASS (complex of proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 53 publications
7
82
0
Order By: Relevance
“…Nup98 is one of the mobile and peripheral FG (Phe-Gly domain) nucleoporins and is located at both the nuclear and cytoplasmic sides of the NPC central channel [4,5]. Arabidopsis Nup98a (also known as DRA2) is also found distributing in different subcellular compartments [6].…”
Section: Nup98 Proteins Mainly Localize To the Nuclear Membrane And Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Nup98 is one of the mobile and peripheral FG (Phe-Gly domain) nucleoporins and is located at both the nuclear and cytoplasmic sides of the NPC central channel [4,5]. Arabidopsis Nup98a (also known as DRA2) is also found distributing in different subcellular compartments [6].…”
Section: Nup98 Proteins Mainly Localize To the Nuclear Membrane And Nmentioning
confidence: 99%
“…NPC is built by at least 30 unique proteins (nucleoporin, Nup) which are highly conserved in eukaryotic cells [2,3]. Nup98 is a mobile and peripheral FG (for Phe-Gly domain) nucleoporin and spans from the nucleus to cytoplasmic of the central channel of the NPC [4,5]. Arabidopsis thaliana Nup98a (also known as DRA2) is also found in different subcellular locations [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using both mouse hematopoietic progenitor cells (HPCs) and immortalized human cells as a model, Franks et al (2017) explored both how Nup98 promotes gene activation in normal cells and (using Nup98-Nsd1) how Nup98 fusion proteins promote aberrant gene activation (Franks 2017). Chromatin immunoprecipitation combined with high-throughput sequencing of Nup98 in wild-type mouse HPCs revealed that Nup98 binding correlated with trimethylation of H3K4 even more so than transcription factors such as HOXB4 that are associated with active promoters within the nucleoplasm in HPCs.…”
mentioning
confidence: 99%
“…Previous work had suggested critical roles for the interaction of Nup98 fusion proteins with the nuclear exportin Crm1 (Oka et al 2016) and the H3K4 methyltransferase MLL1 (Xu et al 2016) to recruit Nup98 to chromosomal sites, promoting AML. The study by Franks et al (2017) proposes an additional/alternative explanation for the downstream effects of recruitment of Nup98 fusion proteins to chromatin, raising a number of interesting questions that will be addressed in the future. First, how is Nup98 recruited to particular chromosomal loci in both normal cells and AML?…”
mentioning
confidence: 99%